2019
DOI: 10.1186/s42506-019-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, tension-type headache, and depression among Saudi female students in Taif University

Abstract: BackgroundStudies done in Saudi Arabia showed a high prevalence of headache among university students. Limited research was done to assess the relationship between headache and psychiatric disorders. The aim of this study was to assess the prevalence and association between migraine, tension-type headache, and depression among Saudi female students in Taif University.Participants and methodsA cross-sectional study using self-administered questionnaires about headache and depression was conducted at the Taif Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
6
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 28 publications
7
70
6
5
Order By: Relevance
“…The results showed that the prevalence of primary headaches in students was 60.7%, corroborating the studies conducted in Turkey 7 and Saudi Arabia 9 . Concerning the type of headache, as in the literature, stress headaches and migraines occur most frequently among university students, regardless of gender [21][22][23] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed that the prevalence of primary headaches in students was 60.7%, corroborating the studies conducted in Turkey 7 and Saudi Arabia 9 . Concerning the type of headache, as in the literature, stress headaches and migraines occur most frequently among university students, regardless of gender [21][22][23] .…”
Section: Discussionsupporting
confidence: 86%
“…Various international epidemiological studies have investigated the prevalence of headaches among university students. The prevalence of migraines among them was 7.9% in Southeast China 6 ; 17.8 in Turkey 7 and 14.0% in Iran 8 and 32.5% in Saudi Arabia 9 , 24.0% in Brazil 10 . Data on headaches calculated 68.4% in Saudi Arabia 9 , 22.6% in Turkey 7 , and 32.0% in Brazil 11 .…”
Section: Introductionmentioning
confidence: 97%
“…We included the following studies, comparison among students of all 5 years and those not being enrolled yet (premedical year students),[ 29 ] comparative studies between medical and non-medical students,[ 30 31 ] an article applying migraine, tension headache, and depression. [ 32 ]…”
Section: Methodsmentioning
confidence: 99%
“…It also accompanies nausea or vomiting. 14 According to estimates TTH is the third most common disorder in the world. 15 Post-traumatic headache (PTH) is defined as the one which begins within seven days of Traumatic brain injury, and further is subdivided into acute form and chronic form, acute form is when pain disappears within three months of trauma, and chronic, when headache persists beyond this period.…”
Section: Introductionmentioning
confidence: 99%